Effect of Castration on Bone Healing in Male Rabbit Model; Clinical, Histopathological and Radiological Study - Ahlam J. AL-Khamas; Zainab J. Malik (Institute of Medico-legal Publications Pvt Ltd, 2021)
Twenty male rabbits were used in the current study. The rabbits were classified into two groups (castrated and un-castrated). Injected by solution consists from Ketamine HCL (40 mg /Kg/B.W/IM) and xylazine HCl (20mg /Kg B.W/IM). The first group was uncastrated while the second group was castrated and waiting one month. For both groups, at the middle of lateral aspect of the femoral region, a 5mm in diameter bore in the femoral bone was made by a medical drill device. The clinical signs showed some manifested such as pain, edema and fever in the castrated group more than the un-castrated group. The last clinical signs disappeared during two to three days in the un-castrated group and (5-7) days in the control group. Examination of radiological of both groups revealed reaction of the periosteal was begin at 2nd week in the second group while in the castrated group which started at the ending of 3rd week in the first group. The fracture was disappeared at 4th week in the second group. The bony mass was redesigned into the lamellar bone in 4th week in the second group, that characterized by adhesion of the bone with the external callus. Our study showed that the fracture healing morebest quantity and quality in the second group than in the first group. The histopathological examination showed osteoclast, osteoblast and the periosteal reaction started at (15-30) days after operation more in the second group than the first group. Moreover, the osteocytes is a presence in more in the uncastrated group than the first group.